Sport participation behaviours of spectators attending major sports events and event induced attitudinal changes towards sport. Issue 2 (5th June 2017) - Ramchandani, Girish; Coleman, Richard J.; Bingham, Jerry
Abstract : Purpose: Evidence of the link between major sports events and increased participation at grassroots level is somewhat mixed. The purpose of this paper is to examine attitudinal changes to sport participation among spectators associated with seven sports events held in Great Britain in 2014. Design/methodology/approach: Primary data were gathered from 4, 590 spectators aged 16 and over who attended one of the events. Both positive (inspiration) effects and negative (discouragement) effects were considered through the lens of the transtheoretical model (TTM). Findings: The evidence from this research indicates that event audiences belong primarily to the latter (more active) stages of the TTM. It was also found that attending sports events can further fuel the existing desire of contemplators to increase participation, whereas the catalytic effect among pre-contemplators is arguably less potent. Virtually no discouragement effects were observed across the different TTM stages. Research limitations/implications: The research stops short of measuring actual changes in sport participation post-event of individuals in the different TTM stages and any attribution of such behaviour changes to events. This is both a limitation of the current research and a natural direction for future research. Practical implications: The main implications for promoting sport participation through the medium of sports events include attracting more people in the early stages of the TTM, greater collaboration between different event stakeholders and the building of sport participation strategies into the event planning phase. Originality/value: Models of behaviour change such as the TTM have seldom been applied to document the current and/or planned sport participation behaviour of individuals in a sport event context or to examine attitudinal changes towards sport as a result of attending an event. An adapted version of the TTM has been proposed to overcome the limitations of the traditional model.